Регіональні особливості балад українців румунської Добруджі - Лєснікова, Г. (Матеріали до української етнології, 2007)
In this article, we propose the methods of analysis of the regional peculiarity of the song folklore (based on the ballads of Ukrainian from the Romanian Dobrudsha).